2016
DOI: 10.5194/tc-10-2485-2016
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular composition of terrestrial and marine organic matter in sediments across the East Siberian Arctic Shelf

Abstract: Abstract. Mobilisation of terrestrial organic carbon (terrOC) from permafrost environments in eastern Siberia has the potential to deliver significant amounts of carbon to the Arctic Ocean, via both fluvial and coastal erosion. Eroded terrOC can be degraded during offshore transport or deposited across the wide East Siberian Arctic Shelf (ESAS). Most studies of terrOC on the ESAS have concentrated on solvent-extractable organic matter, but this represents only a small proportion of the total terrOC load. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 65 publications
5
24
1
Order By: Relevance
“…The comparison of the distribution of bulk OC with terrOC revealed that the high OC concentrations on the outer eastern East Siberian Sea shelf are probably to a large part caused by marine primary production, since terrOC concentrations in that area are rather low. This agrees with previous findings reporting the inflow of nutrient-rich Pacific waters westward up to around 160°E (Anderson et al, 2011;Semiletov et al, 2005;Sparkes et al, 2016;Tesi et al, 2014).…”
Section: 1029/2018gb005967supporting
confidence: 93%
See 2 more Smart Citations
“…The comparison of the distribution of bulk OC with terrOC revealed that the high OC concentrations on the outer eastern East Siberian Sea shelf are probably to a large part caused by marine primary production, since terrOC concentrations in that area are rather low. This agrees with previous findings reporting the inflow of nutrient-rich Pacific waters westward up to around 160°E (Anderson et al, 2011;Semiletov et al, 2005;Sparkes et al, 2016;Tesi et al, 2014).…”
Section: 1029/2018gb005967supporting
confidence: 93%
“…These numbers and patterns are similar to previous estimates of the terrOC contribution in surface water POC (Semiletov et al, 2012). This agrees with previous findings reporting the inflow of nutrient-rich Pacific waters westward up to around 160°E (Anderson et al, 2011;Semiletov et al, 2005;Sparkes et al, 2016;Tesi et al, 2014). They were highest close to the Lena River delta and northward (roughly along 130°E).…”
Section: 1029/2018gb005967supporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the East Siberian coastline contains large Ice Complex Deposits (ICD; also known as "Yedoma"). These Plio-Pleistocene permafrost deposits are weakly lithified and rich in well-preserved OC, providing a major influx of sediment and carbon to the Arctic Ocean (Bischoff et al, 2016;Lantuit et al, 2013;Schirrmeister et al, 2008Schirrmeister et al, , 2011Strauss et al, 2012Strauss et al, , 2013Sparkes et al, 2016;Vonk et al, 2010Vonk et al, , 2012.…”
Section: Study Areamentioning
confidence: 99%
“…The seabed consists of permafrost that developed sub-aerially, was flooded during Holocene sea-level rise and is now being buried by sediment sourced from fluvial and coastal erosion (Kienast et al, 2005). Geochemical studies investigating the sources and offshore distribution of organic matter have noted differences between east and west, nearshore and offshore sections of the shelf (Bischoff et al, 2016;Karlsson et al, 2015;Semiletov et al, 2005;Sparkes et al, 2015Sparkes et al, , 2016Tesi et al, 2014).…”
Section: Study Areamentioning
confidence: 99%